Effective Solutions for Implementing Android-Based Computer-Based Testing (CBT) In Vocational High Schools as A Digital Assessment Innovation - Tiur Malasari Siregar; Dian Armanto; Suci Frisnoiry; Dede Ruslan (Postgraduate, University of Mataram, 2025)
The rapid development of information technology currently demands a transformation in the education assessment system, especially in Vocational High Schools (SMK). One of the challenges faced is the limited facilities and infrastructure such as computer laboratories that are not comparable to the number of students, so that the implementation of computer-based test (CBT) is less than optimal. The aim is to develop an Android-based CBT assessment system that is integrated with the Case Method in the Business Economics subject in SMK. This innovation is designed so that students can take exams anytime and anywhere, without being constrained by limited computer devices or internship schedules. The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development method with the Waterfall Development Model approach to build the system. The developed system was validated by material and media experts, followed by small-scale and large-scale trials on class XI students of SMK Negeri 14 Medan. This Android-based CBT system is effective and feasible to use. In terms of usability, this system received a positive response from students, with high scores on indicators of ease of use, speed of access, and time efficiency. The integration of Case Method- based questions has also been shown to improve students' understanding in solving real problems in the field of Business Economics. The CBT system based on Android integrated with Case Method is able to be an effective solution to overcome the limitations of facilities and infrastructure in vocational schools. The implications provide significant contributions in supporting the digitalization of education and improving the quality of learning evaluation in schools.